Urgensi budaya literasi masyarakat Indonesia - Ulya, Diah Mariatul (Maliki Interdisciplinary Journal, 2023)
The era of globalization requires humans to master increasingly developing technology. This fast-paced era change can generate opportunities if used wisely, but can become a source of disaster if not anticipated. Mastery of technology for everyone should require skills in literacy in order to be able to identify problems and synthesize information that is increasingly spreading in the digital era. However, the literacy culture of Indonesian society is very low. Indonesia ranks 60th out of 61 countries in the world. This condition is very concerning when considering that Indonesia is the fourth most populous country in the world. Factors that influence the lack of literacy culture in Indonesia include internal and external factors. A reading culture should be instilled and nurtured from an early age, meaning that the role of parents and the surrounding environment greatly influences this culture. The author uses descriptive analysis and data collection techniques through literature studies. The purpose of making this article is that the Indonesian people are able to identify problems, efforts to form the character of youth who love literacy, counteract conflicting ideologies, and ward off rampant hoax news.